Memberdayakan Berpikir Kritis Siswa melalui Model Pembelajaran Contextual Teaching And Learning (CTL) dengan Media Torso Ditinjau dari Gaya Kognitif Reflektif dan Impulsif - Vista Indahwati; Imas Cinta Mulya (Universitas Sebelas Maret, 2017)
This study aims to describe students' critical thinking ability in biology learning through Contextual Teachig and Learning (CTL) learning model with Torso media in review of reflective cognitive style and impulsive cognitive style. The subjects of this study were VIII MTS Muhammadiyah 01 Karangagung students from 2016 to 2017 who had been given cognitive tests using Matching Familiar Figure Test (MFFT) consisting of 17 students with 9 reflective cognitive-style children and 8 impulsive cognitive-style children. Data analysis on students' critical thinking was analyzed using Non Parametric Statistics analysis technique with Mann Whitney Test. The results of this study indicate that there are differences in the way children think critically reflective cognitive style and impulsive cognitive style, children who have reflective cognitive style have the ability to think critically better than the child's cognitive impulsive style. So Based on the results of data analysis and discussion of the results of research can be concluded that the critical thinking skills of cognitive reflective-style students better than students who have impulsive cognitive style on the biology of learning through the model Contextual Teachig and Learning (CTL) by using Torso media.